Isotopic Variability in Arctic Precipitation as a Climatic Indicator - Moorman, Brian; Michel, Frederick; Drimmie, Robert (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Preliminary data are examined from a project in which the variability in the isotopic composition of precipitation across northern Canada and the implications for paleoclimatic reconstruction are examined. The data set shows a geographic variability of about 6%o in isotopic composition of precipitation across the Canadian Arctic, roughly double the temporal variability seen in the ice corerecords from the last 10,000 years. The seasonal variability in average monthly ä1âÏ values from the arctic stations in 1991 was as much as 26%o. A snow and firn core collected on Bylot Island had arange of 14.8%0, compared to the range in average monthly precipitation of 25.6%o covering the same time period.This difference in the observed seasonal range of values is the result of processesoperating in the snow pack, such asvapor movement and molecular diffu-sion, and the strategy used in sampling the core. The results indicate that a much better understanding of the geographic and seasonal variation in the ä180 values of precipitation is required before a direct linkage between the isotope records inice cores and global climate change can be determined. Using recently developed radiocarbon dating techniques, buried glacier ice that has been preserved in permafrost may be able to provide the greater spatial and temporal detail required.